Remodelamento do proteoma cardíaco em resposta ao treinamento aeróbico em um modelo de hipertrofia cardíaca - Tatiane de Oliveira Barreto (2017)
Cardiac hypertrophy is an adaptive process of the myocardium that results in an increase in heart mass and may be associated with an increased risk of morbidity and mortality. Aerobic training can promote cardiovascular, metabolic and autonomic benefits; therefore, it has been used as a non-pharmacological alternative in the prevention and treatment of this condition. A comparative proteomic approach, by two-dimensional gel electrophoresis coupled with mass spectrometry (MALDITOF/TOF), was used to investigate the effects of aerobic exercise on cardiac proteome remodeling of pathological isoproterenol-induced left ventricular hypertrophy in mice. C57Bl/6 mice were divided into four experimental groups: sedentary healthy (SH), trained healthy (TH), sedentary isoproterenol (SI) and trained isoproterenol (TI). The animals of the SI and TI groups received daily subcutaneous injection of isoproterenol for 10 consecutive days (45 mg/kg/day). All animals were submitted to a maximum treadmill stress test to determine the training load and assess individual physical performance. The animals of the TH and TI were submitted to a moderate-intensity training on the treadmill for eight weeks. After the training protocol, all animals were resubmitted to a maximum stress test. Histological analysis of the left ventricular myocardium demonstrated integrity of the architecture of the cardiac muscle and muscle cells in healthy animals - SH and TH - with a slight hypertrophy in the latter group, thus providing evidence that aerobic exercise training can induce physiological hypertrophy. In contrast, isoproterenol-treated mice - SI and TI - showed pathological hypertrophy in the left ventricle with severe myofiber disorganization and fibrosis areas, which wasless severe in the tissue of animals of the group submitted to aerobic training - TI. Such results point to both the possibility of inducing pathological hypertrophy by isoproterenol and the beneficial effect of aerobic training on pathological hypertrophy. Sedentary animals with pathological hypertrophy had lower aerobic capacity, which confirmed the detrimental effect of isoproterenol administration on the conditioning of these animals. Aerobic training improved the aerobic capacity of both healthy animals and animals with pathological hypertrophy, which confirms the importance of physical exercise in cardiac rehabilitation. The protein profile of the LV revealed a different expression of 105 protein spots between the groups, and 58 proteins were identified and belong to the following functional classes: energy metabolism, oxidative stress, heat shock and structural proteins. Pathological hypertrophy negatively modulated the expression of proteins involved in energy metabolism, while physiological hypertrophy positively modulated the expression of the same proteins. The same could be observed in animals with pathological hypertrophy in response to aerobic training. However, both hypertrophies resulted in an increase in the expression of heat shock and structural proteins. Two of the identified proteins - sarcalumenin and PP1ɣ - are important for excitation-contraction coupling, which increase in expression in response to aerobic training and act in cardiac cytoprotection, being responsible for the improvement of the cardiac function and conditioning of the animals with pathological hypertrophy. Therefore, the results suggest that aerobic training induces the remodeling of the cardiac proteome in pathological hypertrophy, thus constituting an important instrument in treating and preventing this condition.